(untitled) (Swiss Medical Weekly, 2013)
Mantle cell lymphoma (MCL) is a relatively rare lymphoma entity accounting for an estimated 3%–6% of all non-Hodgkin’s lymphoma cases. Characterised by both the incurability of indolent lymphomas and the rapid growth of aggressive lymphomas, MCL has a median overall survival of only 4–5 years. Although the disease often shows an encouraging response to first-line treatment, its clinical course is usually marked by recurrent relapses, resulting in a dismal long-term outcome. The choice of therapy for managing the disease is a complex problem that still requires evidence-based guidance. Owing to the rarity of MCL, the bulk of data comes from phase II trials in small numbers of patients. Nevertheless, therapeutic strategies for MCL have evolved in an effort to adapt treatment according to the individual patient’s risk profile, and the overall survival has nearly doubled in the last 30 years. The use of effective immunochemotherapy regimens in first-line therapy, advances in stem cell transplantation, and the development of more active salvage therapy regimens have improved the outcome. This review will summarise the key factors that drive clinical practice with respect to the management of MCL.